OVERVIEW OF VEHICLE TRANSPORTATION PROCEDURES ABOVE KMP. SATRIA PRATAMA ON THE KUALA TUNGKAL TELAGA – PUNGGUR BATAM TRACK IN TANJUNG JABUNG BARAT REGENCY, JAMBI PROVINCE - Elfita Agustini; Febriansyah Febriansyah; Bayi Budiansyah (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2021)
Kuala Tungkal Ferry Port is a Ferry Port that serves inter-island crossings between provinces. The Kuala Tungkal Ferry Port is managed by the West Tanjung Jabung Regency Transportation Service. In the transportation system, security and safety are highly favored as a form of good service delivery. However, the loading of vehicles on ships operating at the Kuala Tungkal Ferry Port is not in accordance with the standards set out in the Regulation of the Minister of Transportation Number 115 of 2016 concerning Procedures for Transporting Vehicles on Ships and Regulation of the Minister of Transportation Number 30 of 2016 concerning Obligations to Bind Vehicles. On Crossing Transport Ships. This study aims to determine the existing conditions for the transportation of vehicles on the Satria Pratama Crossing Motor Ship in accordance with the Regulation of the Minister of Transportation Number 115 of 2016, implementing vehicle binding obligations according to Ministerial Regulation Number 30 of 2016 and evaluating the needs of vehicle binding officers needed to improve the transportation system. aboard the Satria Pratama Ferry Motor Ship. The research methodology used is observation, survey and documentation. Then to analyze this, it is guided by the Regulation of the Minister of Transportation Number 115 of 2016 and the Regulation of the Minister of Transportation Number 30 of 2016. The results of this study are that the existing condition of the procedure for transporting vehicles on the Satria Pratama Crossing Motor Ship is still not in accordance with the Regulation of the Minister of Transportation Number 115 of 2016, the obligation to tie up vehicles on the Satria Pratama Ferry Motor Vessel is still not in accordance with the Regulation of the Minister of Transportation Number 30 of 2016 and the need for an ideal vehicle binding officer is 2 vehicle binding officers.